2014
DOI: 10.1186/1471-2202-15-88
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation leads to a loss of functional connectivity in frontal brain regions

Abstract: BackgroundThe restorative effect of sleep on waking brain activity remains poorly understood. Previous studies have compared overall neural network characteristics after normal sleep and sleep deprivation. To study whether sleep and sleep deprivation might differentially affect subsequent connectivity characteristics in different brain regions, we performed a within-subject study of resting state brain activity using the graph theory framework adapted for the individual electrode level.In balanced order, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 46 publications
5
95
0
2
Order By: Relevance
“…These results are also consistent with existing (Van Dongen et al 2003). Recent research has found that sleep deprivation decreases activation of and functional connectivity in the prefrontal cortex, which may explain the specificity of cognitive deficits in higher-order processes, such as inhibition and attention, following sleep loss (Ma et al 2015;Verweij et al 2014). Furthermore, the latent executive function variable was also associated with the latent maladaptive repetitive thought variable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are also consistent with existing (Van Dongen et al 2003). Recent research has found that sleep deprivation decreases activation of and functional connectivity in the prefrontal cortex, which may explain the specificity of cognitive deficits in higher-order processes, such as inhibition and attention, following sleep loss (Ma et al 2015;Verweij et al 2014). Furthermore, the latent executive function variable was also associated with the latent maladaptive repetitive thought variable.…”
Section: Discussionsupporting
confidence: 90%
“…In conjunction with extant research, these results suggest that sleep disturbance may impair executive function, which may then lead to increased engagement in maladaptive repetitive thought. It may be the case that the decreased activation of and functional connectivity within brain regions associated with executive function observed following sleep loss (Ma et al 2015;Verweij et al 2014) may contribute to a diminished ability to inhibit engagement in maladaptive repetitive .46…”
Section: Discussionmentioning
confidence: 98%
“…Dynamic changes in drift ratio during sleep deprivation or night work are associated with reduced signal-to-noise ratio and, consequently, degraded quality of cognitive processing. This perspective is supported by neuroimaging data, which indicate that sleep deprivation is associated with a reduction in neuronal connectivity (Verweij et al, 2014) or available functional neuronal circuits, especially those that are most intensively used for the task at hand (Chee & Asplund, 2013). …”
Section: Discussionmentioning
confidence: 88%
“…Indeed, changes in vigilance and arousal (hereafter described jointly as "arousal"), which can be especially prevalent during the passive and uncontrolled resting state, result in fMRI signal variability that may confound the extraction of functional networks (5,19). For example, the amplitude and extent of correlations in restingstate fMRI data vary with EEG-and behaviorally defined indicators of drowsiness and light sleep (20)(21)(22)(23)(24)(25) and are altered by sleep deprivation (26)(27)(28) and caffeine-induced changes in arousal state (29). Distinct patterns of functional connectivity across multiple networks have been associated with distinct EEG-defined sleep stages (30,31) with sufficient reliability to enable the identification of sleep stages from fMRI data alone (30).…”
mentioning
confidence: 99%